Does Financial Distress Using Altman Z-Score Capital Affect Stock Price? - Ichsani, Sakina; Wahju Widajatun, Vincentia; Hertina, Dede (International Journal of Psychosocial Rehabilitation, 2020)
Changes in stock prices that occur in the capital market can be influenced by various factors, including internal factors and external factors. The failure of the company can be seen from financial conditions that are not good and the company’s stock price that continues to fall or experience stagnation. If this condition is not immediately addressed by the company, the company may be able to experience the condition of bankruptcy or financial distress. The purpose of this study is to determine the effect of the Altman Z-Score ratio, which consists of working capital to total assets, retained earnings to total assets, earnings before interest and tax to total assets, market value to book value of debt, and sales to total assets to stock prices. The results of the study show that simultaneously the variables forming the Altman Z-Score affect the stock price by 30.83%. While partially only variables sales to total assets that have no influence on stock prices. The suggestion of this study is that companies and potential investors always pay attention to the financial performance of textile and garment companies, while the suggestion to other researchers is to use other financial distress models that affected stock prices.